2021
DOI: 10.1111/jvh.13583
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus care cascade in persons experiencing homelessness in the United States in the era of direct‐acting antiviral agents: A scoping review

Abstract: The hepatitis C virus (HCV) care cascade has been well characterized in the general United States population and other subpopulations since curative medications have been available. However, information is limited on care cascade outcomes in persons experiencing homelessness. The main objective of this study was to map the available evidence on HCV care cascade outcomes in people experiencing homelessness in the U.S. in the era of direct‐acting antiviral agents (DAAs). Primary and secondary outcomes included l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…Overall, by ITT, 70.4% of patients with active hepatitis C infection were treated in our project. These results are substantially higher than in previous studies that included the classic referralbased or institutional-based management of hepatitis C (care cascade) with rates of less than 50% (23)(24)(25). We believe this increase is due to the adaptable (and relatively rapid) stepwise and simplified cascade of mobile on-site screening, reflex HCV RNA testing, and treatment being given outside of the hospital, demonstrable in our study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Overall, by ITT, 70.4% of patients with active hepatitis C infection were treated in our project. These results are substantially higher than in previous studies that included the classic referralbased or institutional-based management of hepatitis C (care cascade) with rates of less than 50% (23)(24)(25). We believe this increase is due to the adaptable (and relatively rapid) stepwise and simplified cascade of mobile on-site screening, reflex HCV RNA testing, and treatment being given outside of the hospital, demonstrable in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…In our study, most patients who received treatment achieved SVR (ITT 72.8% and per protocol 90.2%). These results are lower than those in the general population (2) but similar to those reported in marginalized populations (23–25). A recent study conducted at 4 large shelters in San Francisco and Minneapolis which aimed to evaluate the effectiveness of low-barrier linkage to HCV therapy among individuals accessing homeless shelters, showed a SVR rate of 81.8%.…”
Section: Discussionsupporting
confidence: 58%
“…Our analysis is subject to a few limitations. First, general evidence exists that there are key subgroups beyond PWID, MSM, and low SES TW that bear increased burden of HCV in San Francisco, including Blacks/African Americans, people with a history of injection drug use (but not injecting drugs in the last 12 months), people who are currently or formerly incarcerated, and people who are currently or formerly unhoused [ 5 , 52 ]. However, the inability to estimate prevalence of HCV seropositivity, chronic infection, or treatment for these subgroups using local data meant they were lumped into the “general population” age and sex strata.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, DAA treatment uptake was reported in 45% of current injectors (2018) 12 and an Australian study observed that 34% of PWID with hepatitis C started DAA treatment between 2014 and 2018 11 . In the US, treatment uptake amongst people experiencing homelessness was a rate‐limiting step along the care cascade, with 5%–59% of those chronically infected starting DAAs 13 . A recent meta‐analysis of 20 population‐based studies reporting the HCV care cascade (published 2017–2020) 14 found DAA uptake in PWID ranged between 13% in the US, 37% in Australia, 40% in Canada and 50% in Georgia.…”
Section: Introductionmentioning
confidence: 99%
“…11 In the US, treatment uptake amongst people experiencing homelessness was a rate-limiting step along the care cascade, with 5%-59% of those chronically infected starting DAAs. 13 A recent meta-analysis of 20 population-based studies reporting the HCV care cascade (published 2017-2020) 14 found DAA uptake in PWID ranged between 13% in the US, 37% in Australia, 40% in Canada and 50% in Georgia. DAA treatment uptake rates are falling in high income countries and 76% of these are not on track to achieve elimination targets, according to updated analyses.…”
Section: Introductionmentioning
confidence: 99%